Kenneth Cragg on Muslim-Christian Relations (Al-Qamar, 2020)
This era of Muslim-Christian relationship is deeply indebted to such scholars who, from their Christian point of view, have given a fresh air and deeper understanding of Islam. They have advocated the element of love and sympathy in their research. They have illuminated the hidden values and profound meaning of Islamic religion. It means that there is a space for an apology for apologetic thinkers. Kenneth Cragg was one among these soft minded scholars who addressed the Christian world to retake the Muslim world in a way which is acceptable for Muslims. Kenneth Cragg was an Evangelical upbringing Bishop, Missionary and professor.  His field of research was Semitic religions but his main focus was Muslim-Christian relations. He wrote more than sixty books and mostly is on Islam, in which he mostly discussed those matters which are similar in Islam and Christianity, especially according to the Quran and Gospel.  Both the sides accused him, Christian said: that he was giving priority to Quran over New Testament and the Muslim scholars blamed him that he was Christianizing Islam, but he looked sincere to create harmony between Islam and Christianity. In this paper we critically analyze his views about Muslim –Christian relationship.
Keywords: Kenneth Cragg; parameters; Christianity and Islam; relationship